Dinâmica salarial dos trabalhadores da agropecuária brasileira: uma análise de dados espaciais (1992-2009) - Estanislau, Patricia (2011)
The objective of this work is to examine the wages differences dynamics of the farming sector temporary and permanent workers, through the analysis of the wage behavior in the Brazilian states on the period from 1992 to 2009. For this it was used the Space Data Exploratory Analysis (AEDE), the space econometrical modeling and as source of data the National Research of Sample of Domiciles (PNAD). It was used convergence tests β absolute, conditional convergence β and convergence σ. To the conditions of the conditional convergence β process were used the variables: schooling average, experience (to catch the human capital effect) of each segment of workers and tractor power (to catch the fixture capital effect). The AEDE disclosed the wages distribution of the permanent and temporary workers to the Brazilian states. The states that better remunerate their permanent workers were placed in Center West region, South region and the state of São Paulo, the worse incomes were in the Northeast region. For the temporary workers the best wages were situated in the regions North and Center West, and the lowest incomes in the Northeast region. It was evidenced positive special autocorrelacion of the farming workers wages demonstrating that the space localization of these wages interfere in its values. The High-High clusters formations type for the farming workers (permanent and temporary) were placed in the North, Center West and South regions. Low-Low clusters formations type concentrate in states of the Northeast region of Brazil. In the bivaried space autocorrelação the farming workers wages follow the same behavior. The relation between wage and schooling have positive association, when the wages relate with experience they showed negative and when wages were compared to fixture capital the space association was positive. For the wage distribution of the wages growth tax of these workers, we notice that states with lower wages have higher growth taxes (Santa Catarina, Minas Gerais, Goiás, Distrito Federal, Piauí and Paraíba) of those states that had higher wages than in parts had its growth taxes lower (Roraima, Amapá), showing evidences of the convergence existence. Applying the space imbalance model it was proved the absolute convergence existence, indicating that the permanent and temporary workers wages go through a common stationary state between the Brazilian states. In the conditional convergence we notice that the convergence speed is increased for the temporary permanent workers. The only significant variable was the farming worker schooling (permanent and temporary) disclosing that the wage inaqualities between the states tend to diminish. The significant space effect indicates the existence of two distinct works markets in the Brazilian farming. The fixed effect coefficient is significant and positive and shows the work market particularitity of each Brazilian state. The convergence σ of the temporary and permanent workers wages of the Brazilian farming shows the reduction of the wage inaquality by the fall in the dispersion of wage levels. However we suggest a reflection about the politics adopted in the farming, that could stimulate the inaquality wage reduction by politics that stimulate the instruction and qualification of this worker, and to be developed with locacional character, so that the Northeast region could increase its wage levels.